ENHANCEMENT OF SOURDOUGH BREAD USING PROBIOTIC LACTIC ACID BACTERIA ISOLATED FROM CORN STEEP LIQUOR - Racheal Oluwayemisi FASHOGBON; Bukola Margaret POPOOLA; Oyindamola John SAMSON; Faith Opeyeoluwa AKINDIRAN; Ismail Oladimeji AKINWUNMI; Olusola Abayomi OJO-OMONIYI (Food and Environment Safety)
Fermented Zea mays (OGI), an edible paste made from fermented grains specific to the region, is an integral part of the human diet. Corn steeping liquor (CSL) is an important by-product obtained from the wet milling of Zea mays. The present study was conducted to investigate the probiotic characteristics and in vitro antibacterial activity of lactic acid bacteria (LAB) obtained from CSL, as well as their impact on the quality of sourdough bread. A total of 46 LAB were isolated and evaluated for their probiotic potential. The probiotic potential of LAB was determined by evaluating their hemolytic capacity, bile salt resistance, phenol tolerance, antimicrobial and antioxidant activities. The lactic acid bacteria with the most promising probiotic potential were molecularly characterized and used for the production of sourdough bread (SDB). Conventional microbiological methods identified Lactobacillus plantarum (21%), Lactobacillus fermenti, and Leuconostoc mesenteroides (17%) as the predominant LAB species. Twelve LAB showed signs of gamma hemolysis. It is noteworthy that isolate CSL23 showed the highest bile tolerance, while isolates CSL15, CSL23, and CSL6 demonstrated the highest phenol tolerance. Isolates CSL15, CSL23, and CSL29 showed significant inhibition zones of 15.00 ± 0.18 mm, 20.5 ± 0.26 mm, and 22.60 ± 0.31 mm against four tested pathogens, in addition to effective antioxidant scavenging activity. Molecular identification revealed that LAB isolates CSL15, CSL23, and CSL29 were Lactiplantibacillus plantarum ROF4, Lactiplantibacillus plantarum ROF5, and Lactiplantibacillus plantarum ROF6, respectively. This finding indicates that all LAB strains belong to the same genus. Therefore, it is evident that the current study demonstrated that Lactiplantibacillus plantarum strains isolated from CSL have the potential to serve as promising probiotic starter cultures that could be used in the production of sourdough bread with improved functional properties.